2021
DOI: 10.5194/acp-21-8615-2021
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the quasi-biennial oscillation response to stratospheric aerosol modification depending on injection strategy and species

Abstract: Abstract. A known adverse side effect of stratospheric aerosol modification (SAM) is the alteration of the quasi-biennial oscillation (QBO), which is caused by the stratospheric heating associated with an artificial aerosol layer. Multiple studies found the QBO to slow down or even completely vanish for point-like injections of SO2 at the Equator. The cause for this was found to be a modification of the thermal wind balance and a stronger tropical upwelling. For other injection strategies, different responses … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 51 publications
2
30
0
Order By: Relevance
“…Similar inter-model spreads have been reported in the recent literature for CMIP6 models for both effective equilibrium climate sensitivity (ECS; the equilibrium warming for a doubling of CO 2 ; see Zelinka et al, 2020) and transient climate response (TCR; the temperature warming with a doubling of CO 2 in a scenario with a 1 % per year CO 2 increase; see Meehl et al, 2020). Some models (amongst them CESM2(WACCM) and UKESM1-0-LL, also present in this study) have been found to have values well above previously established likely ranges for both ECS and TCR (Gettelman et al, 2019;Sherwood et al, 2020). Some of the relationships between the variables reported in Table 2 are explored in Fig.…”
Section: Magnitude Of Geoengineering Requiredsupporting
confidence: 63%
“…Similar inter-model spreads have been reported in the recent literature for CMIP6 models for both effective equilibrium climate sensitivity (ECS; the equilibrium warming for a doubling of CO 2 ; see Zelinka et al, 2020) and transient climate response (TCR; the temperature warming with a doubling of CO 2 in a scenario with a 1 % per year CO 2 increase; see Meehl et al, 2020). Some models (amongst them CESM2(WACCM) and UKESM1-0-LL, also present in this study) have been found to have values well above previously established likely ranges for both ECS and TCR (Gettelman et al, 2019;Sherwood et al, 2020). Some of the relationships between the variables reported in Table 2 are explored in Fig.…”
Section: Magnitude Of Geoengineering Requiredsupporting
confidence: 63%
“…The MAECHAM5-HAM (Niemeier et al, 2020;Niemeier and Timmreck, 2015;Stier et al, 2005) and SOCOL-AER 5 models (Feinberg et al, 2019;Stenke et al, 2013) share the same dynamical core from MAECHAM5 (Roeckner et al, 2003;Roeckner et al, 2006) and used the same horizontal resolution (T42 or 2.8°x2.8° in longitudes and latitudes) and model top (0.01 hPa or approximately 80 km). However, the MAECHAM5-HAM model uses 90 vertical levels and internally generates a quasi-biennial oscillation (QBO), which has been found in several studies to modify the effects of geoengineering injections (Aquila et al, 2014;Richter et al, 2017;Niemeier et al, 2020, Franke et al, 2021. The SOCOL-…”
Section: Nudgedmentioning
confidence: 99%
“…The AM-H 2 SO 4 scenarios were designed to minimize the growth in average particle size as a function of injection rate, since sulfur is added to each grid box as particles of approximately 0.1 µm radius which grow mainly by coagulation. In addition, 10aerosol heating in the tropical lower stratosphere increases the strength of the Brewer-Dobson circulation, resulting in greater lofting in the tropical stratosphere which, for accumulation mode and smaller particles, (Niemeier et al, 2020), can prolong the residence time for 25 Tg(S) yr -1 injections relative to 5Tg(S) yr -1 injections though the details of this process are model dependent and include changes in the QBO for the CESM2 and MAECHAM5-HAM models (Franke et al, 2021).…”
Section: Changes In Global Aerosol Propertiesmentioning
confidence: 99%
See 2 more Smart Citations